2007
DOI: 10.1371/journal.pmed.0040064
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Mycobacterium ulcerans Lesion Development by Exposure to Aquatic Insect Saliva

Abstract: BackgroundBuruli ulcer is a severe human skin disease caused by Mycobacterium ulcerans. This disease is primarily diagnosed in West Africa with increasing incidence. Antimycobacterial drug therapy is relatively effective during the preulcerative stage of the disease, but surgical excision of lesions with skin grafting is often the ultimate treatment. The mode of transmission of this Mycobacterium species remains a matter of debate, and relevant interventions to prevent this disease lack (i) the proper understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…In contrast to previous reports, access to drinkable water 1 did not seem to be associated with BU, and our data do not suggest that wearing clothes during farming activities is protective against BU. This could fit with the hypothesis of a possible immune protection against BU provided by frequent insect bites, 8 but the most likely explanation is that subjects with BU typically wear clothes to hide skin lesions. Our data were collected through a questionnaire.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast to previous reports, access to drinkable water 1 did not seem to be associated with BU, and our data do not suggest that wearing clothes during farming activities is protective against BU. This could fit with the hypothesis of a possible immune protection against BU provided by frequent insect bites, 8 but the most likely explanation is that subjects with BU typically wear clothes to hide skin lesions. Our data were collected through a questionnaire.…”
Section: Discussionsupporting
confidence: 55%
“…Mycobacterium ulcerans, the causative agent of Buruli ulcer, colonizes the salivary glands of N. cimicoides. Between 5% and 10% of N. cimicoides that are captured in endemic areas are infected with M. ulcerans 88 . Immediately after ingestion, M. ulcerans translocates from the head capsule to the coelomic cavity.…”
Section: Immune Defences In the Gutmentioning
confidence: 99%
“…It has been demonstrated that animals preexposed to ticks were protected from tularemia (15) and borreliosis (16,17), and vaccination with a tick salivary cement protein protected mice against the lethal effect of tick-borne encephalitis virus (18). Preexposure to mosquito saliva through bites led to partial protection against Plasmodium berghei infection (19) and immunization with the saliva of an aquatic insect (Naucoris genus) protected mice against Mycobacterium ulcerans infection (20).…”
mentioning
confidence: 99%